2006
DOI: 10.1177/174578660601700403
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement – the Emergence of a New Construct?

Abstract: Employee engagement is a useful recent concept in HRM: it is a composite construct that describes inter alia employees' commitment, job satisfaction and involvement. Increasingly, employee engagement has also come to be recognised as making a significant difference to performance at all levels within the company. But there still exists some vagueness about the meaning of the term: how exactly may employee engagement be defined? This article presents a genealogy of the new construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A number of empirical studies have been done on the relationship between job satisfaction and employee engagement and other related constructs. Work has been done on antecedents of job satisfaction and engagement (Mcbain, 2006; Schleicher et al, 2004; Yeh, 2013). However, little research has been carried to study levels of job satisfaction among working employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of empirical studies have been done on the relationship between job satisfaction and employee engagement and other related constructs. Work has been done on antecedents of job satisfaction and engagement (Mcbain, 2006; Schleicher et al, 2004; Yeh, 2013). However, little research has been carried to study levels of job satisfaction among working employees.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Burke and MacDermid (1999) conducted a study and found that there is a negative relationship between workaholism and job satisfaction. Mcbain (2006), in his study, reported that senior executes of an organization are highly engaged with their work; however, employees of line level and hourly paid have the least level of involvement or engagement with organizations. Supervisors have the tendency of being strongly enthusiastic and persistent, are more motivated, and have the intensity and concentration in their work in comparison with employees of line level.…”
Section: Job Satisfaction and Work Engagementmentioning
confidence: 96%
“…The concept of Employee engagement is evolving in many fields such as human resources, employee relations, organizational behaviour, development and organisational [8] The two main points of debate around engagement are: Firstly, engagement is considered as collection of behaviours that not limited to being engaged but also includes the behaviours which might track back from this state (such as focused performance). Many authors support this argument such as [9 10].…”
Section: Introductionmentioning
confidence: 99%
“…M. Bakker, (2006) said that working engagement is characterized by high energy levels and can be identified with one's work. Mcbain (2006) (Salanova, 2008). Kahn (1990) argued that engagement can utilize members of the organization in working roles in which they will use and express themselves physically, cognitively, emotionally, and mentally during performing their roles.…”
Section: Engagementmentioning
confidence: 99%